Developing and analysing different definitions of operational excellence - Kai Mueller; Eckehard Müller (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
Operational Excellence is an expression, which is used in many ways in the context of transforming a company to play a relevant roll on the market in the future. A basic question is if these words are only a hype or does a scientific background exist? How is operational excellence is defined? An investigation is made to answer these questions and try to define operational excellence in the background of the actual developments.
Keywords: 330; Operational excellence; Definition; Tools